Modeling and simulation of an antenna with optimized AMC reflecting layer for gain and front-to-back ratio enhancement for 5G applications. (April 2020) - Hocini, A; Melouki, N; Denidni, T A
Abstract: A low-profiled microstrip patch antenna for application in the 5G wireless communication systems is backed by a reflecting layer based on an optimized artificial magnetic conductor (AMC) to enhance the gain and the front-to-back ratio. The design and analyses process were carried out using the full-wave commercial simulator CST Microwave Studio in parallel with Matlab, using the embedded CST to Matlab VBA-based interface to create an automated simulation environment and to design both a conventional antenna and the proposed one. A genetic algorithm (GA) is used to optimize the AMC reflecting layer to achieve maximum gain and front-to-back ratio around the frequency band of interest. The results yield an important enhancement in the peak gain and front-to-back ratio, alongside a low side-lobe level (SLL) due to the successful surface waves suppression, thus making this antenna design a good candidate for future wireless communication systems.